LO39: Systematic review of emergency department practice change interventions for improving asthma outcomes. (May 2019) - Hurley, K.; Fitzpatrick, E.; MacEachern, L.; Curran, J.
Abstract : Introduction : Emergency departments (ED) play a vital role in asthma care for patients of all ages. Our objective was to review and synthesize all practice change interventions in ED settings that focused on improving the health outcomes of adults and children with asthma.Methods : This study was a systematic review adhering to the methods outlined by the Effective Practice and Organization of Care (EPOC) Cochrane Review Group. We developed a search strategy with a library scientist for the following databases: AMED, CINAHL, Embase, ERIC, MEDLINE, HealthStar, CENTRAL, DARE and Cochrane's EPOC and Airways registers. We also hand searched the Journal of Asthma, Pediatrics and Chest. Two reviewers independently reviewed titles, abstracts and full text using predetermined criteria. Data were extracted by two independent reviewers who used a structured abstraction form and assessed risk of bias. All discrepancies were resolved by consensus.Results : Our search strategy yielded 8, 878 titles and abstracts for review. A total of 214 studies underwent full text screening and we extracted data from 27 studies. Risk of bias was judged as low in 10 studies, moderate in 8 studies and high in 9 studies. A range of interventions were employed, with education (n = 14) and reminders (n = 8) being the most prevalent. In pediatric settings, most studies targeted changing the behaviour of parents (n = 11). Four studies targeted health care providers and four studies targeted both providers and parents. We identified a major deficit in the use of behaviour change theory to guide intervention design. The most common primary outcomes of interest were unscheduled return visits (n = 14), primary care follow-up (n = 9), quality of life (n = 5) and ED length of stay (n = 4). We were not able to perform a meta-analysis due to heterogeneity in interventions and outcomes.Conclusion : Although we found a range of interventions used to improve asthma care in EDs, there was significant variation in reported primary outcomes. Both unscheduled return visits and primary care follow-ups, the most common primary outcomes, varied in the timeframe and manner in which they were collected. Most interventions were educational and based on an assumption that education would change behaviour. Future research in this ares would benefit from standardized outcome measures and intervention designs based upon models of behaviour change model.